Crystal structure of 6-oxo-4-phenyl-1-propyl-1,6-dihydropyridine-3-carbonitrile, C15H14N2O - Shi Bei-Chen; Chen Hao-Dong; Zhu Xian-Dui; Zhang Meng-Meng; Zhang Zhi-Fei (Zeitschrift für Kristallographie - New Crystal Structures)
C15H14N2O, orthorhombic, P212121 (no. 19), a = 7.6510(15) Å, b = 11.465(2) Å, c = 14.526(3) Å, V = 1274.2(4) Å3, Z = 4, Rgt(F) = 0.0422, wRref(F2) = 0.1199, T = 296 K.